2006
DOI: 10.1080/13682820600623911
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language therapy service delivery for bilingual children: a survey of three cities in Great Britain

Abstract: There is a need for a change in how data on linguistic diversity in society are collected and disseminated, both at a national level and within SLT services, so that informed decisions can influence the future of quality services to minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 7 publications
1
23
0
1
Order By: Relevance
“…In the United States, a lack of understanding of these issues has resulted in disproportionate placement of Latino children in special education and related services (Artiles, Rueda, Salazar, & Higareda, 2005; de Valenzuela et al, 2006). Similar patterns of disproportionate representation of bilingual children in special education programs have been documented in the United Kingdom (Mennen & Stansfield, 2006; Stow & Dodd, 2003; Winter, 1999), Singapore (Gupta & Chandler, 1993), Australia (McLeod & McKinnon, 2007), Sweden (Berhanu, 2008; Salameh, Nettelbladt, Håkansson, & Gullberg, 2002), and Hong Kong (Cheuk, Wong, & Leung, 2005). …”
Section: Test Performance In Bilingual Childrensupporting
confidence: 61%
“…In the United States, a lack of understanding of these issues has resulted in disproportionate placement of Latino children in special education and related services (Artiles, Rueda, Salazar, & Higareda, 2005; de Valenzuela et al, 2006). Similar patterns of disproportionate representation of bilingual children in special education programs have been documented in the United Kingdom (Mennen & Stansfield, 2006; Stow & Dodd, 2003; Winter, 1999), Singapore (Gupta & Chandler, 1993), Australia (McLeod & McKinnon, 2007), Sweden (Berhanu, 2008; Salameh, Nettelbladt, Håkansson, & Gullberg, 2002), and Hong Kong (Cheuk, Wong, & Leung, 2005). …”
Section: Test Performance In Bilingual Childrensupporting
confidence: 61%
“…Over the past decade, SLPs' practices with children with SSD have been described based on surveys undertaken in countries including the US (Brumbaugh & Smit, 2013;Caesar & Kohler, 2009;Lof & Watson, 2008;Roseberry-McKibbin, Bruce, & O'Hanlon, 2005;Skahan, Watson, & Lof, 2007), the UK (Joffe & Pring, 2008;Mennen & Stansfield, 2006), Australia (McLeod & Baker, 2004;Watts Pappas, McLeod, McAllister, & McKinnon, 2008;Williams & McLeod, 2012), the Netherlands (Priester, Post, & Goorhuis-Brouwer, 2009), and internationally (Jordaan, 2008). These surveys have revealed that SLPs' assessments typically include administration of a commercial assessment tools, consideration of intelligibility, stimulability, and hearing screening (Skahan et al, 2007).…”
Section: Surveys Of Slps' Practices With Children With Ssdmentioning
confidence: 99%
“…Yet, the socio‐cultural approach may not in itself solve the totality of problems associated with other approaches. However, Mennen and Stansfield (2006) comment that many SLTs lack knowledge about languages and cultures other than their own. The majority of SLTs in the UK are white, middle‐class and women (Cortazzi and Jin 2004).…”
Section: Assessment Challengesmentioning
confidence: 99%